Analysis Intrinsic Elements In The Twilight Movie: Eclipse - Mardhiyatul Hasanah Millenia; Ria Kamilah Agustina (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to identify the fundamental components of the Twilight film. The intrinsic technique was employed in this study to identify the fundamental components of the Twilight movie. This research is types of qualitative research, according to Leavy in (Umboro, 2021) design this study used a qualitative research approach to obtain the data needed that is in line with the objectives. This study explain the intrinsic elements by used Intrinsic Elements, Plot, Character, Setting, Theme Literature, language and mandate in the movie twilight. This research to find the characteristics Edward Cullen as one of main character of twilight movie. The data of this research were taken from dialogues and narrations of Twilight (2008) film script written by Melissa Rosenberg. As a result, this research showed the intrinsic elements of Twilight film consisting of theme, characters (Bella, Edward, Jacob), setting (place: Bella’s House, Forest, Edward’s House, School, Hospital) (Time: Summer, Rainy, Day Night), Plot (Exposition, Inciting, Moment Complication Stage, Climax, Falling Action), language, moral value.